Challenges and Opportunities of Artificial Insemination on Dairy Cattle in Ethiopia - Mohammed Yousuf (Research Horizon, 2021)
Artificial insemination is very important for genetic improvement, especially in dairy cattle breeds. It has problems in meeting the needs of some producers, not its opportunities. The objective of this study was the challenge and opportunity of artificial insemination on dairy cattle in the case of Sayo district, west Wollega Zone, Ethiopia. The problem of not using Artificial insemination is not limited to the region, and there are also dairy farmers in our district who have not practiced the service due to various challenges. In addition, most of the Artificial insemination services reported by the dairy industry have failed, rather than bull services. However, although there are few attempts to quantify opportunities, constraints, and why producers do not use artificial insemination services in other regions, researchers have not disclosed well-documented data on the challenges and opportunities of artificial insemination services in the Sayo region. The Result is Artificial insemination has played an important role in increasing milk production in the study area because the crossbreed that got good traits from exotic breeds gave high milk than local breed.